2011
DOI: 10.4301/s1807-17752011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Business Intelligence (BI) Implementation from the Perspective of Individual Change

Abstract: Change is central in the implementation of Information Technology (IT). This paper reports on a study in which the aim was to examine the nature of change at the individual level with an analysis based on interviews with representatives from a Business Intelligence (BI) solution provider and a group of clients. The implementations seemed to have occurred without great difficulty, BI learning was quick, intuitive, and the process generated a positive affect. Changes occurred in work practices, in the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Thus, 'mood' is not simply a feeling that accompanies cognition and reasoned action; it is of greater primacy [3:143]. It is the underlying mood that attunes us to a situation and directs our cognitive impression of what is possible and what is impossible, thus moods may be a trigger rather than a by-product of change [12]. "Moods are far from being a marginal, colourful add-on to our mentalistic explanations of how the actors behave in situations.…”
Section: Moodmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, 'mood' is not simply a feeling that accompanies cognition and reasoned action; it is of greater primacy [3:143]. It is the underlying mood that attunes us to a situation and directs our cognitive impression of what is possible and what is impossible, thus moods may be a trigger rather than a by-product of change [12]. "Moods are far from being a marginal, colourful add-on to our mentalistic explanations of how the actors behave in situations.…”
Section: Moodmentioning
confidence: 98%
“…The hospitality metaphor allows us to see the potential risks and ambiguity of the technology as a stranger, rather than seeing it as unequivocal and fixed [17]. Fetzner and Freitas [12] suggest that the use of the hospitality metaphor as a theoretical lens takes into account affective, cognitive and behavioural aspects when studying individual responses to IS innovation. This inclusion of affective factors provides a more holistic view of the IS adoption and innovation process.…”
Section: Hospitality Metaphor As Theoretical Lensmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the aspects mentioned in Table 4, Canes [51] suggests that the main factors influencing the adoption of BI in SMEs are the cost and complexity of BI system, this matches what mentioned Boonsiritomachai [15 ] wh o believes that the BI software systems integrate mathematical functions that make it difficult to use. Howev er, the study of Mesquita [47] showed that after SME owners provided BI training to the staff, they learned to use the BI system more straightforward. Nyblom [31] mentions that hiring qualified personnel in B I knowledge would support the functioning of BI systems.…”
Section: Factors Involved In the Implementation Of Bi In Smesmentioning
confidence: 99%
“…4. Factors that can influence the implementation of BI Factor Reference The existence of a project leader [47] The time that takes implementing a BI project [16,29,47] There is a culture of information valorization [16,35,47,52] Age of the employees [47] The ease of use of the tool [15,31,42,47,51] The capability of the tool to provide quality information [30,47] The lack of knowledge of businesspeople about BI use [26,30,39,47] Skills of the employees of the IT area [30] Availability of BI tools providers [15,30] Ability to afford the costs generated when implementing BI tools [15,20,26,29,30,32,51,52] The existence of an organizational structure [16] Financial support [16] Cost of hiring a specialist for implementing the project [16] Level of managers' compromise to support the introduction of technological innovations [15,16,26] Manager attitude towards BI project [16] On the other hand, the factor that has had the most significant impact in research of BI adoption in SMEs is the capability to pay the generated costs of implementing BI tools [20], the authors argue that usually, large companies are the ones who adopt BI technologies because they have enough resources ...…”
Section: Factors Involved In the Implementation Of Bi In Smesmentioning
confidence: 99%